Evaluation of Delivered Services among Selected Hospital Wards: A Case Study Using Multiple Criteria Decision Making Methods (MCDM) - Milad Shafiee; Mohammad Hossein Ghafoori; Fatemeh Aboee; Sara Forootan; Mohammad Arab (Tehran University of Medical Sciences, 2017)
Abstract   Background and Aim: Especially in the case of Hospital services, quality assesment is an complicated and vague issue. For achieving this goal Multiple Criteria Decision Making methods help us. These studies aims to knowledge and prioritize quality indicators and rank selected inpatient wards in an elected hospital of Tehran university of medical science by using Analytical Hierarchy Process and TOPSIS methods.   Materials and Methods: This is a descriptive-analytical and cross-sectional research. At the first, with an overview of the research literature and expert opinion, indicators of quality assessment were selected. Then we did prioritization of these indicators with using of expert opinion and AHP method. In the final stage, selected inpatient wards the Hospital were ranked in terms of quality of service using TOPSIS by a sample consist of 300 of inpatients.   Results: Eight main domains (Responsiveness, Safety and risk management, Tangibles, attention to patient, Health communications, Competency and professionalism, accessibility, Credit and assurance) were selected for quality assessment. Among these indicators, competency had the highest priority and attention to patient had the lowest priority. Also the department of Heart had the highest quality of service and the department of Neurology had the lowest quality.   Conclusion: According to crucial role of the service quality on patients' satisfaction, the use of appropriate indicators for quality of services, prioritizing them and also proper assessment of the quality of hospital services can play a major role in health policies.